2021
DOI: 10.22246/jikm.2021.42.6.1245
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Feature of Reflux Esophagitis Patients Visiting a Single Korean Medicine Hospital: A Retrospective Study

Abstract: Objectives: This study investigated the clinical characteristics and symptoms of patients with reflux esophagitis (RE) visiting a Korean medicine hospital.Methods: We retrospectively reviewed the medical records of patients with an RE diagnosis who visited a Korean medicine hospital from June 15, 2020, to April 15, 2021. We analyzed the clinical characteristics and the results of a symptoms questionnaire.Results: Our sample included 1,151 patients (711 females). The median age was 58 years; the most common age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…[15] (3) GerdQ [17] : The Korean version of GerdQ consists of 6 items and can be easily administered to suspected GERD patients for initial diagnosis or posttreatment follow-up. [8] The questionnaire comprises of 4 positive predictors of GERD (heartburn, regurgitation, sleep disturbance, and use of over-the-counter medication in addition to that prescribed) and 2 negative predictors of GERD (epigastric pain and nausea). Items were graded; scores ranging from 0 to 3 were applied for the positive predictors and from 3 to 0 for the negative predictors and calculated as the sum of all scores 0 to 18.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] (3) GerdQ [17] : The Korean version of GerdQ consists of 6 items and can be easily administered to suspected GERD patients for initial diagnosis or posttreatment follow-up. [8] The questionnaire comprises of 4 positive predictors of GERD (heartburn, regurgitation, sleep disturbance, and use of over-the-counter medication in addition to that prescribed) and 2 negative predictors of GERD (epigastric pain and nausea). Items were graded; scores ranging from 0 to 3 were applied for the positive predictors and from 3 to 0 for the negative predictors and calculated as the sum of all scores 0 to 18.…”
Section: Methodsmentioning
confidence: 99%
“…[ 7 ] A retrospective study published in 2021 analyzed the medical records of 1151 patients with GERD who received KM including HM at hospital as an intervention for GERD and found that most patients visiting KM hospitals were females in their sixties with chronic and refractory reflux esophagitis. [ 8 ] Several studies have explored the effectiveness of HM interventions for GERD. A case series of patients with GERD treated with Ljintang-Gamibang and acupuncture showed that HM with acupuncture significantly reduced the patients’ symptoms and improved their Quality Of Life (QOL).…”
Section: Introductionmentioning
confidence: 99%